A quantitative assessment of variations in the palm surface area as a percentage of total body surface area within the general population. (2018) - Liu, Tina C.; Bhatt, Rajan; Farrell, Kimberly D.; Baek, Stephen; Liu, Yuk Ming; Abdel-Malek, Karim; Arora, Jasbir
Healthcare professionals who treat burn patients determine fluid requirements for resuscitation based on an estimation of burned body surface area (BBSA) as a percentage of total body surface area (TBSA). Hence, it is important to get an accurate assessment of these values. An overestimation or underestimation of the BBSA percentage can lead to medical complications, negatively affecting a patient's quality of care. Conventional methods to estimate the BBSA percentage include segmenting the three dimensional body surface into a two-dimensional burn chart or estimating the area relative to the palm of the hand with the assumption that the palm represents 1% of the TBSA. These methods introduce inaccuracies due to unreliable assumptions and estimations. For example, methods that rely on a burn chart overgeneralise that the body type of a patient to fit the established body sections in the chart, and methods that use the palm of the hand rely on incorrect assumptions regarding the palm surface area. This paper demonstrates specifically that the assumption that a patient's palm can be estimated as 1% of the TBSA is not reliable. In addition, it summarises, evaluates, and quantifies these inaccuracies, and compares and contrasts the variations for different genders.